REVIEW OF DECISIONS IN DEFAULT CASES COMPANIES AGAINST WORKERS IN THE PERSPECTIVE OF THE AUTHORITY TO ADJUDICATE DISTRICT COURTS AND INDUSTRIAL RELATIONS DISPUTES - Hani Usmandani; Nurjannah Septyanun; Yulias Erwin (Jurnal Ilmiah Advokasi, 2024)
The subject matter of this study is related to the legal relationship between the Company and workers in the decision of the Company's default case against workers and the application of the authority to adjudicate in the decision of a quo case. This research is qualitative research with normative (doctrinal) research type. Using the Legislation approach, conceptual approach, and case approach. Data collection techniques through literature studies, as well as analytical descriptive analysis and deductive methods. The results of the research on the legal relationship between the Company and Workers are based on the Collective Labor Agreement stipulated in Law Number 13 of 2003 concerning Manpower Jo. Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law and the authority to adjudicate cases of default of the Company against Workers is the authority of the Industrial Relations Court. The District Court does not accept a quo lawsuit because a default dispute is a dispute of rights as referred to in Article 1 point 2 of Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes.    Keywords: Authority; Judge; Worker; Dispute; default